JUVENILE SEX OFFENDER REHABILITATION: HOW THE US APPROACH CAN HELP INDONESIA SATISFY ITS COMMITMENT TO RESTORATIVE JUSTICE PRINCIPLES - Amanda, Putri Kusuma (UI Scholars Hub, 2014)
In July 2012, Indonesia enacted landmark legislation to reform the juvenile justice system. The Juvenile Justice Act is a break through which constituted to protect the rights of children in the juvenile justice system. This Act explicitly includes the principle of restorative justice, a principle that guarantees the government’s commitment to use rehabilitative and restorative approaches. The question that arises now is how this law can be satisfied through the implementation of the Act. Specifically, this paper will focus on how the restorative justice principle can be applied to juvenile commit sexual offense. This paper, learning from the United State’s rehabilitation system, will offer some suggestions to form the rehabilitation process for juvenile sex offenders in Indonesia, such as enhancing research about juveniles commit sexual offense, improving the law and regulation, and implementing counseling, supervised group homes, and other support mechanisms.